STEVE and the Picket Fence: Evidence of Feedback‐Unstable Magnetosphere‐Ionosphere Interaction. Issue 24 (23rd December 2019) - Mishin, Evgeny; Streltsov, Anatoly
Abstract: This paper aims to extend the understanding of Strong Thermal Emission Velocity Enhancement (STEVE) and the Picket Fence related to strong subauroral ion drifts (SAID). We numerically demonstrated that precipitating energetic electrons are critical for the structuring of the Picket Fence. It is created by feedback‐unstable magnetosphere‐ionosphere interactions driven by the SAID electric field when the Hall conductance created by energetic ( ≥ 1 keV) electrons exceeds the Pedersen conductance. We show that thermal excitation of the red‐line emission in STEVE is inhibited by inelastic collisions with molecular nitrogen. Suprathermal ( ≤ 500 eV) electrons coming from the turbulent plasmasphere appear to be the major source. We also show that the chemiluminescencent and radiative attachment reactions do not explain the short‐wavelength part of the STEVE continuum and argue that accounting for vibrational excitation may resolve the problem. Atmosphere's upwelling due to enhanced ion‐neutral drag leads to the increased abundance of molecular components relative to atomic oxygen. Key Points: Feedback‐unstable magnetosphere‐ionosphere interaction in the presence of energetic electron precipitation explains the Picket Fence formation Thermal excitation of the red‐line emission in the low‐density SAID channel is inhibited by inelastic collisions with molecular nitrogen To understand the STEVE continuum, transitions between vibrationally excited molecular states in the SAID channel should be taken into account